Clinical Practice Guidelines for Bladder Cancer 2019 update by the Japanese Urological Association: Summary of the revision. (21st June 2020) - Matsumoto, Hiroaki; Shiraishi, Koji; Azuma, Haruhito; Inoue, Keiji; Uemura, Hirotsugu; Eto, Masatoshi; Ohyama, Chikara; Ogawa, Osamu; Kikuchi, Eiji; Kitamura, Hiroshi; Shinohara, Nobuo; Takahashi, Satoru; et al.
Abstract : Objectives: Despite just a 4‐year interval from the last version (2015) of the Clinical Practice Guidelines for Bladder Cancer, several dramatic paradigm shifts have occurred in the latest clinical practice regarding both the diagnosis and treatment of bladder cancer. Herein, we updated the 2019 version of the Clinical Practice Guidelines for Bladder Cancer under the instruction of the Japanese Urological Association. Methods: We previously reported in a revision working position paper for Clinical Practice Guidelines for Bladder Cancer 2019 edition and described the methods of revision detail. Results: The major points of change in the 2019 version are presented and explanations are given as follows: (i) introduction of the new reference assessment system; (ii) modification of the risk classification for non‐muscle‐invasive bladder cancer; (iii) addition of clinical questions for the new tumor‐visible techniques in non‐muscle‐invasive bladder cancer; (iv) inclusion of minimally invasive surgeries for muscle‐invasive bladder cancer and immune checkpoint inhibitors for locally advanced/metastatic muscle‐invasive bladder cancer; (v) overview chapter of the histological variant of urothelial cancer and rare cancers of the bladder; and (vi) recommendation of follow up in non‐muscle‐invasive bladder cancer and muscle‐invasive bladder cancer. Conclusions: Guidelines should be updated based on the current evidence and updates carried out without delay. The hope is that this guidelines will be assessed by many urologists and will be the cornerstone for the next revision.